Multidimensional Analysis of Environmental Literacy (Sensitivity, Knowledge, Belief, and Behavior of Environment) of Prospective Teachers - Samsun Hadi; Abdulkadir Rahardjanto; Moch. Agus Krisno Budiyanto; H. Husamah (IKIP Mataram, 2020)
Sensitivity, knowledge, belief, and behavior to the environment will bring out good behavior that leads to environmental literacy (EL). This study aimed at analyzing the students’ EL based on the multidimensional perspective. This study comprised of two types, namely library and field research. Questionnaire was developed from The Second Minnesota Report Card on EL. This study was conducted in FKIP-UMM at undergraduate level, from July to October 2020. The types of data were in the form of qualitative and quantitative. The data were obtained from the results of Google Form. The population of this study was the students of FKIP-UMM, in which it consisted of 2.750 students. The subjects were chosen randomly by sharing the link of Google Form thru the WhatsApp group so that 139 students (5%) were obtained. The data and EL findings were analyzed descriptively qualitative analytic. Scaling multidimensional analysis was carried out by using ordination that continued with scaling and percentage processes. The results indicated that (1) Environmental sensitivity tends to show various conditions. (2) Environmental knowledge also tends to vary. (3) Environmental beliefs tend to be good. (4) Environmental behavior in students tends to be good.